Linear and nonlinear perturbations in dark energy models - Amendola, Luca (Physical review. D, Particles, fields, gravitation, and cosmology, 2004)
I present linear and second-order perturbation theory in dark energy models with an explicit interaction to matter in view of its application to N-body simulations and nonlinear phenomena. Several new or generalized results are obtained: the general equations for the linear perturbation growth, an analytical expression for the bias induced by a species-dependent interaction, the Yukawa correction to the gravitational potential due to dark energy interaction, and the second-order perturbation equations in coupled dark energy and their Newtonian limit. I also show that a density-dependent effective dark energy mass arises if the dark energy coupling is varying.